Exploring the potential for language supportive learning in English medium instruction: a Rwandan case study. Issue 3 (2nd July 2016) - Milligan, Lizzi O.; Clegg, John; Tikly, Leon
ABSTRACT: This article puts forward the argument for language supportive learning for learners in English medium instruction (EMI) classrooms based on the findings from a mixed methods study in Rwanda. The article first reviews the relevant literature and research which looks at the concept of language support, focusing on textbooks and pedagogy in sub-Saharan African EMI countries. The scant literature which exists suggests that current teaching practice and textbook design are not targeted for learners learning in a second language which frequently results in the global language acting as a major barrier to effective learning across the curriculum. The potential of 'language supportive textbooks and pedagogy' for addressing such a barrier is then considered through an analysis of a recent intervention in Primary 4 Rwandan classrooms. Findings suggest that language supportive learning can lead to significant improvements in learner outcomes and more effective engagement with subjects across the curriculum. Conclusions consider implications for bilingual education policies in Rwanda and further afield.